0.5(2y+9)=0.3(4y-6)

Simple and best practice solution for 0.5(2y+9)=0.3(4y-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.5(2y+9)=0.3(4y-6) equation:


Simplifying
0.5(2y + 9) = 0.3(4y + -6)

Reorder the terms:
0.5(9 + 2y) = 0.3(4y + -6)
(9 * 0.5 + 2y * 0.5) = 0.3(4y + -6)
(4.5 + 1y) = 0.3(4y + -6)

Reorder the terms:
4.5 + 1y = 0.3(-6 + 4y)
4.5 + 1y = (-6 * 0.3 + 4y * 0.3)
4.5 + 1y = (-1.8 + 1.2y)

Solving
4.5 + 1y = -1.8 + 1.2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1.2y' to each side of the equation.
4.5 + 1y + -1.2y = -1.8 + 1.2y + -1.2y

Combine like terms: 1y + -1.2y = -0.2y
4.5 + -0.2y = -1.8 + 1.2y + -1.2y

Combine like terms: 1.2y + -1.2y = 0.0
4.5 + -0.2y = -1.8 + 0.0
4.5 + -0.2y = -1.8

Add '-4.5' to each side of the equation.
4.5 + -4.5 + -0.2y = -1.8 + -4.5

Combine like terms: 4.5 + -4.5 = 0.0
0.0 + -0.2y = -1.8 + -4.5
-0.2y = -1.8 + -4.5

Combine like terms: -1.8 + -4.5 = -6.3
-0.2y = -6.3

Divide each side by '-0.2'.
y = 31.5

Simplifying
y = 31.5

See similar equations:

| 11(v+4)-3v=4(2v+2)-1 | | 2p^2-12p+18=0 | | 6x-6-2x+2=0 | | (-16)-83+(-22)+(-86)= | | 11x+23=2x-1 | | 3x(3x-12)=9(x-4) | | 3x+30+2x-12=180 | | 2x+3x=5x+1/8 | | -9(y+1)=6-8y | | 2.1x+1.3x-4.6=22 | | 20x+18=20x-18 | | .5m+3-5=2 | | 10x+10=10x-10 | | 64s^2-48s+9=0 | | x-2(2x+9)=3-3x | | 2x-4x+1=0 | | 13-x=44 | | 180-x=3x(180-4)+4 | | 5(x+1)=3(x-2) | | x^3-4x^2+49x-196=0 | | X^2+5x-e^3=0 | | -5(4-5p)=7p-38 | | 180-x=2(90-x)+25 | | 2(x+3)=2(x+7) | | -4(6y-9)-y=-2(y-3) | | 3+2n-1=7n+4-4n | | 2u-(8)+3v= | | 2x-4+0.5x+0.2(2x-4+8)=26 | | (2x+7)6=-7x+4 | | 2u-8+3v= | | 8(x+7.4)-8x+12= | | 37x+8=6(6x+1) |

Equations solver categories